Determinants of Growth in an Error : Correction Model for El Salvador - Mendez Morales, Armando (IMF Working Papers; Working Paper, 1998)
An error-correction model identifies determinants of growth consistent with results from panel regressions based on a standard Cobb-Douglas production function for El Salvador for 1970-1995, with structural factors affecting the technology variable and macroeconomics and expectations explaining the deviations from the long-run trend. Consistency of the parameters is satisfactory, especially considering that half of the sample period was affected by a civil war, 40 percent of the working population migrated to foreign countries during that period, and the rapid process of economic reform after the advent of peace resulted in overlapping structural patterns.